Forecasting of reliability indicators of information systems with thermoelectric devices - Зайков, Владимир Петрович; Мещеряков, Владимир Иванович; Гнатовская, Анна Арнольдовна (Eastern-European Journal of Enterprise Technologies, 2012)
The model of interrelation of indicators of reliability and the basic significant parameters of the two-cascade thermoelectric cooling device with consecutive electric connection of cascades is offered. Parities for definition of indicators of reliability two-cascade thermoelectric device, working in a mode of the greatest refrigerating factor are received